25 spesies burung liar - Jasmi Abdul (Kuala Lumpur : Dewan Bahasa dan Pustaka, 2016)
On birds species in Malaysia.
Includes bibliographical references (pages 207-209) and index.
In Malay.
Keywords: Birds -- Malaysia -- Identification